2020
DOI: 10.3390/diagnostics10080556
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation of Extra-Abdominal Desmoid Tumors: A Single-Center Experience with Literature Review

Abstract: Cryoablation (CA) has gained popularity in the treatment of benign and malignant musculoskeletal tumors. While extra-abdominal desmoid (EAD) tumors are not malignant, they remain challenging to treat because of their high local recurrence rate. We reviewed all EAD tumors treated with CA at our institution between November 2012 and March 2020. Fourteen procedures were performed on nine females and one male (mean age, 33 ± 18 years) as either first-line (n = 4) or salvage therapy (n = 6) with curative intent (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 32 publications
0
36
0
2
Order By: Relevance
“…7 studies recorded both the pre-ablation mean tumor diameter and volume [ 20 , 22 25 , 27 , 28 ], while 1 study recorded only the pre-ablation tumor volume [ 26 ] and 1 study only recorded pre-ablation tumor diameter [ 21 ]. Volume was assessed in different ways, either by an ellipsoid formula, a modified ellipsoid formula (½ x (length x width x height)), manual segmentation or automated software measurement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 studies recorded both the pre-ablation mean tumor diameter and volume [ 20 , 22 25 , 27 , 28 ], while 1 study recorded only the pre-ablation tumor volume [ 26 ] and 1 study only recorded pre-ablation tumor diameter [ 21 ]. Volume was assessed in different ways, either by an ellipsoid formula, a modified ellipsoid formula (½ x (length x width x height)), manual segmentation or automated software measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Volume was assessed in different ways, either by an ellipsoid formula, a modified ellipsoid formula (½ x (length x width x height)), manual segmentation or automated software measurement. 2 studies utilised the ½ x (length x width x height) formula [ 20 , 27 ], 1 study utilised the ellipsoid formula [ 22 ], 3 studies utilised manual segmentation [ 23 , 25 , 28 ] and 1 study used IntelliSpace Discovery software platform (Philips Healthcare) semi-automatic 3D segmentation tool [ 26 ]. 1 study did not mention the method of volume measurement [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tremblay et al 22 described a rate of 6.7% for major complication and a rate of 13.3% for mild complications. Saltiel et al 33 reported 2 major complications out of 14 ablation procedures. We contend that the low levels of complications and the absence of any major complications in the current study may be attributed to the advanced preoperative planning and intraoperative monitoring that were implemented.…”
Section: Discussionmentioning
confidence: 99%